(untitled) (Journal of Academic Research, 2025)
The study aimed to examine the extent to which the prerequisites for implementing e-commerce are available in Libyan commercial banks operating in the city of Misurata. To achieve the study objectives, the researchers employed a descriptive-analytical approach and utilized a questionnaire as the primary data collection tool. A total of 60 questionnaires were distributed to the study sample, which included branch managers, their assistants, department heads, and accountants in Libyan commercial banks operating in Misurata. All questionnaires were fully retrieved, achieving a 100% response rate. The collected data were analyzed using descriptive statistical methods such as frequencies, percentages, means, and standard deviations. To test the study hypotheses, a one-sample *t*-test was applied. The findings revealed that the essential prerequisites for applying e-commerce are available in Libyan commercial banks operating in Misurata, represented by (technical capabilities, administrative and human resources, security and legal dimensions, as well as partnership and integration in banking operations). The results of this study contribute to enriching scientific research in this field.